N-Acetylglucoseamine modified alginate sponges as scaffolds for skin tissue engineering - Demirbilek, Murat; Turkoglu Lacin, Nelisa; Akturk, Selcuk (Tubitak Scientific & Technological Research Council Turkey, 2017)
In the treatment of dermal wounds, wound-dressing materials prepared from natural mucopolysaccharides are widely used because of their advantages such as nonirritation, nontoxicity, and ease in topical application. In the present study, alginate hydrogels modified with N-acetyl glucose amine (NAG) were prepared as wound-dressing material. Physical, chemical, thermal, and mechanical properties of the hydrogels were studied. Cytotoxicity of the hydrogels on endothelial (HUVEC) and keratinocyte (HaCaT) cells were examined. Anti-and proinflammatory cytokine levels of human monocyte-macrophage cells (THP-1) stimulated with hydrogels were determined. According to the results, increasing the NAG concentration led to an increase in the swelling and nitrogen ratios in the hydrogels. Additionally, increasing the NAG concentration decreased elastic modulus and degradation time. Hydrogels were not cytotoxic on HaCaT and HUVEC cells. It stimulated IL-10 and TNF-alpha levels at a small rate.
Keywords: Biomaterials; alginate hydrogels; hyaluronic acid monomers; cytokines; HYALURONIC-ACID; IN-VITRO; EXTRACELLULAR-MATRIX; CHRONIC WOUNDS; TNF-ALPHA; KAPPA-B; HYDROGELS; EXPRESSION; CHITOSAN; CYTOTOXICITY; Life Sciences & Biomedicine - Other Topics